P‐120: Degradation Mechanism and Lifetime Improvement of Blue Quantum‐Dot Light‐Emitting Diodes. Issue 1 (29th May 2019) - Ding, Wen-Cheng; Lee, Chun-Yu; Chen, Chia-Hsun; Huang, Li-Jen; Kuo, Ya-Pei; Chen, Peng-Yu; Lu, Hsueh-Hsing; Lee, Jiun-Haw
Abstract : We have demonstrated that degradation of the hole‐transporting layer material in the blue quantum‐dot light‐emitting diode (QLED) is the main reason accounts for the efficiency loss operated under constant current driving, and the operation lifetime can be elongated by 85% under pulse‐mode driving compared to DC case.